2023
DOI: 10.3389/fphar.2023.1239025
|View full text |Cite|
|
Sign up to set email alerts
|

Unveiling the therapeutic potential of exogenous β-hydroxybutyrate for chronic colitis in rats: novel insights on autophagy, apoptosis, and pyroptosis

Rasha Abdelhady,
Sameh Saber,
Mustafa Ahmed Abdel-Reheim
et al.

Abstract: Ulcerative colitis (UC) is a chronic relapsing inflammatory disease of the colorectal area that demonstrates a dramatically increasing incidence worldwide. This study provides novel insights into the capacity of the exogenous β-hydroxybutyrate and ketogenic diet (KD) consumption to alleviate dextran sodium sulfate (DSS)-induced UC in rats. Remarkably, both interventions attenuated disease activity and colon weight-to-length ratio, and improved macro and microstructures of the damaged colon. Importantly, both β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 67 publications
2
2
0
Order By: Relevance
“…KDs, especially LA-KD, protected the mice from these changes. This is in line with the findings of Kong et al [10] and Abdelhady et al [9] who reported less inflammatory cell infiltration in DSS-treated rodents fed KDs with unknown fat sources. On the other hand, Li et al [11] showed LA-rich KD to promote immune cell infiltration and epithelial damage in DSS colitis.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…KDs, especially LA-KD, protected the mice from these changes. This is in line with the findings of Kong et al [10] and Abdelhady et al [9] who reported less inflammatory cell infiltration in DSS-treated rodents fed KDs with unknown fat sources. On the other hand, Li et al [11] showed LA-rich KD to promote immune cell infiltration and epithelial damage in DSS colitis.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, our results align with the observations of Kong et al [10] who reported KD to alleviate DSS-induced colitis via microbiota-dependent reduction in colonic group 3 innate lymphoid cells, and Abdelhady et al [9] who observed benefits associated with NLRP3 inflammasome inhibition, decreased apoptosis, and increased autophagy. Thus, our findings contradict those of Li et al [11] who reported KD to worsen outcomes in the same model of colitis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations